The Effect of the ICARE Model in the Context of Pagaralam Coffee on Students’ Mathematical Communication Skills in the Topic of Ratios in Year 7 at MTs Al Ikhlas Tanjung Sakti PUMI - Icha Febrianti; Novi Susanti; Reza Lestari (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2026)
Mathematical communication remains one of the most persistently underdeveloped competencies among secondary school students, yet plays a crucial role in developing students' capacity to express and reason mathematical ideas meaningfully. This study examines the efficacy of the ICARE instructional model, embedded within the Pagaralam coffee context, on the mathematical communication competencies of seventh-grade students at MTs Al Ikhlas Tanjung Sakti PUMI. Grounded in constructivist learning theory, the ICARE model (comprising Introduction, Connection, Application, Reflection, and Extension) facilitates meaningful learning through active knowledge construction and contextual engagement. Mathematical communication is understood in accordance with the NCTM framework as the ability to express, represent, and reason mathematical ideas coherently. This study employed a quantitative experimental design with a Pretest-Posttest Control Group approach. Class VII.1, comprising 23 students, served as the experimental group, while Class VII.2, comprising 20 students, served as the control group. Data were collected through mathematical communication assessments and analyzed using an independent two-sample t-test. The results revealed a mean posttest score of 70.39 for the experimental group, with 69% of students attaining a "good" rating, considerably surpassing the mean posttest score of 52.95 and the 52.86% satisfactory rating recorded in the control group. This difference was statistically significant, with a t-value of 3.474 exceeding the critical threshold of 1.683, leading to the rejection of the null hypothesis. These findings confirm that the integration of the ICARE model within the Pagaralam coffee context produced a significant improvement in students' mathematical communication skills in proportional reasoning.